PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP PEMBANGUNAN LAB UNP - Fauziah, Hilma (Departemen Matematika, 2023)
Learning math requires problem-solving skills. In practice, kids’ mathematical problem-solving skills are still low. End-of-even semester results of class VII pupils at UNP Laboratory Development Junior High School in 2022/2023 and the initial test of ability demonstrate low mathematical problem-solving skills. Problem-based learning (PBL) can help pupils solve arithmetic issues. Descriptive and quasi-experimental Static-Group Comparison Design study. Sampling was saturated. Experimental class VIII A and control class VIII B. According to the research, students who learn with the Problem Based Learning (PBL) model perform better than those who use the conventional model (P-value = 0,024 < = 0,05).Keywords – Mathematical Problem-solving, Problem Based Learning